2015
DOI: 10.1007/s11427-015-4946-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial expression of Drosophila Neurexin during the life cycle visualized using a DNRX-Gal4/UAS-reporter

Abstract: Drosophila neurexin (DNRX) plays a critical role in proper architecture development and synaptic function in vivo. However, the temporal and spatial expression pattern of DNRX still remains unclear. For this study, we generated a novel Drosophila transgenic strain termed the DNRX-Gal4 transgenic line, with characteristic features in agreement with the endogenous DNRX expression pattern. DNRX expression was examined by driving the expression of a GFP reporter (nuclear-localized and membrane- localized GFP) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…3 , B–B ″). Previously, we found that DNRX could also be detected in a small subset of peripheral nervous system neurons ( 9 , 38 ). Because of the low sensitivity of the DNRX antibody, we used motor neuron-specific Gal4 (OK6-Gal4) to drive DNRX expression and found that DNRX and Scribble were co-localized at NMJs of Drosophila ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…3 , B–B ″). Previously, we found that DNRX could also be detected in a small subset of peripheral nervous system neurons ( 9 , 38 ). Because of the low sensitivity of the DNRX antibody, we used motor neuron-specific Gal4 (OK6-Gal4) to drive DNRX expression and found that DNRX and Scribble were co-localized at NMJs of Drosophila ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Loss of function of Scribble causes numerous defects in the nervous system, including alterations in synaptic architecture and function. DNRX is abundantly expressed in neurons in the central nervous system and plays important roles in associative learning in Drosophila ( 9 , 20 ), and DNRX can also be detected, and it functions in the Drosophila NMJ ( 21 , 37 , 38 ). Thus we hypothesized that DNRX functions together with Scribble.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are still several remaining questions as to how this cell adhesion molecule that is primarily thought to function at the synapse may contribute to broad systemic alterations in nutrient homeostasis. In Drosophila, Nrx-1 is expressed broadly across the central and peripheral nervous system, as well as in the muscle, gut and neuromuscular junction ( 42 , 47 , 88 ). Thus, it is possible that Nrx-1 could regulate energy metabolism by regulating synaptic transmission within a neuronal population involved in metabolic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The learning experiments were performed as described by Sun and Tully [27,28] Briefly, 3- to 5-day-old male flies were used in learning experiments, they were sequentially exposed to 2 odors (Benzaldehyde, BEN, Sigma, hong kong, China #B1334 and 3-Octanol, OCT, Sigma #218405) for 60 s each. The concentrations for 2 different odors (BEN and OCT) were used when tested flies show an equal preference for both odors.…”
Section: Methodsmentioning
confidence: 99%